A cross-sectional survey of the perspectives of older people in the Scottish Highlands on the management of their chronic pain. (23rd January 2020) - Stewart, Derek; Rushworth, Gordon; Bailey, Nicola; Pfleger, Sharon; Jebara, Tesnime; Munro, Kim; Youngson, Elaine; Wilson, Martin; MacLeod, John; Cunningham, Scott
Abstract: Background: Although there is evidence of suboptimal outcomes in older people with chronic pain, little emphasis has been placed on those in remote and rural settings. Objective: To describe the perspectives of older people in the Scottish Highlands on their chronic pain management. Design: Cross-sectional survey. Setting: NHS Highland, the most remote and rural geographical health board in Scotland. Subjects: Home-dwelling members of the public aged ≥70 years. Methods: Anonymised questionnaires were mailed to a random sample of 1800 older people. Questionnaire items were demographics, nature of any chronic pain, management regimens and perceived effectiveness. Validated scales were the Pain Disability Questionnaire and the Tampa Scale for Kinesiophobia. Results: Adjusted response rate was 39.3% (709/1755). One-quarter (25.0%, n  = 177) were experiencing chronic pain, being more likely to live in deprived areas ( P  < 0.05). Median pain intensity was 6 (IQR 4–7, 10 high), causing distress (median 5, IQR 3–7). Respondents largely consulted GPs (66.1%, n  = 117) with a minority (16.4%, n  = 29) referred to a specialist pain clinic and few consulting other health professionals. Over three quarters (78.0%, n  = 138) were receiving prescribed medicines, most commonly paracetamol, alone (35.6%, n  = 63) or in combination with opioids (16.4%, n  = 29). One-third (31.6%, n  = 56) expressed a desire for more effective medicines; few reported using any non-pharmacological therapies. The median scores for the Pain Disability Questionnaire and Tampa Scale for Kinesiophobia were 74 (IQR 34–104.5, 150 high) and 40 (IQR 35–45, 68 high). Conclusions: Evidence of provision of appropriate integrated and person-centred chronic pain care is lacking.